The effects of narrative care combined with life review on psychological distress, meaning in life, and quality of life in advanced cancer patients receiving hospice care: a randomized clinical trial - Wang, Juan; Xia, Yuan; Cheng, Qinqin; Chen, Ling (Frontiers in Psychology, 2025)
ObjectiveTo investigate the effects of narrative care combined with life review among patients with advanced cancer.MethodsNinety patients who met the inclusion criteria were recruited from the palliative medicine ward of a tertiary-level oncology specialty hospital in Xinjiang and the community hospitals hosted by our hospital from January 2024 to January 2025. This study is a randomized controlled single-blind study. They were randomly divided into control and experimental groups (n = 45 patients per group). The control group received usual care, whereas the experimental group received narrative nursing combined with life review as a psychological intervention in addition to the usual care received by the control group. The number of interventions per patient was not less than 4 times, and the intervention period was 2 weeks. Before and after the intervention, the experimental and control groups were evaluated using the Psychological Distress Management Screening Tool, the Sense of Meaning of Life Scale for Advanced Cancer Patients, and the EORTC Quality of Life Measurement Scale QLQ-C30.ResultsEighty-three participants completed the study. No statistically significant differences were observed in psychological distress, scores for the total meaning of life scale and its individual dimensions, and scores for the total quality of life scale and its individual dimensions between the two groups before the intervention (p > 0.05). After the intervention, the distress thermometer scores were significantly lower in the experimental group than in the control group (p < 0.05). The scores for the total meaning of life scale and its individual dimensions were significantly higher in the experimental group than in the control group (p < 0.05). The scores for the total quality of life scale and its individual dimensions were significantly higher in the experimental group than in the control group (p < 0.05).ConclusionNarrative nursing combined with life review can effectively alleviate the psychological suffering, increase the sense of meaning of life to a certain extent, and improve the quality of survival among patients with advanced cancer. It is recommended to incorporate it into routine hospice care practice, through structured life review guidance, to help patients affirm their self-worth and enhance their dignity and calm at the end of life.